Experiment Tests on Single Phase Inverter Using Raspberry Pi - Zulkifli, Shamsul Aizam (International Journal of Integrated Engineering, 2017)
This project is about a single phase inverter that was developed and used to understand the concept of inverter output pattern for step and square output voltage using Raspberry Pi as the microcontroller. It also includes a technique of communications between the Raspberry Pi and the MATLAB Simulink software and the usage of the Arduino as an analog to digital converter for the inverter. The main idea is to use the low cost microcontrollers which are the Raspberry PI and Arduino in order to generate a suitable switching signal to the inverter based on the instruction developed in the MATLAB-Simulink blocks without any programming framework. This inverter has been tested in two conditions, where the first test was on the switching logic controller for step inverter output and the second test was using the mathematical equation blocks diagram of the inverter for generating a square output voltage. Both tests have been conducted in closed loop voltage feedback mode. At the end, the results show, the selected microcontrollers can be used for generating the controlling switching signal and also to be as an ADC converter for closed loop operation that will be good for the beginner user to understand the process and communication of the microcontroller.